Biological ammonia removal from anaerobically pre-treated landfill leachate in sequencing batch reactors (SBR) - Yalmaz, G; Oztürk, I; Öztürk, İzzet (IWA Publishing, 2001)
The aim of the study was to investigate both the use of the SBR technology in biological ammonia removal from landfill leachate, and the suitability of raw landfill leachate as external carbon source in denitrification step. The SBR was fed with diluted leachate for the first 42 days and then the effluent of UASBR was used as the feed. The SBR was operated intermittently with a cycle time of 24 hours. The effluent NH4+-N values of less than 5 mg NH4+-N L-1 was consistently observed for the initial NH4+-N levels of as high as 1000 mg NH4+-N L-1. The nitrification rates for the first, second and third stages were found as 5.7, 46.8 and 102.8 mg NH4+-N L-1 h-1, respectively. The difference of the nitrification rates in the 2nd and 3rd stages originated from increasing adaptation of the sludge as well as increasing biomass concentration (10.5 mg NH4+-N g-1VSS h-1). No significant accumulation of NO2--N has been observed during the study and NO2--N/NOx--N ratios measured in the 1st aerobic phase and the SBR effluent were less than 7%. The denitrification rates for the second (raw leachate as carbon source) and the third (Ca(CH3COO)2 as carbon source) stages were determined as 45.7 mg NOx--N L-1 h-1 (or 9.85 mg NOx--N g-1VSS h-1) and 125.7 mg NOx--N L-1 h-1 (or 12.88 mg NOx--N g-1VSS h1), respectively.
Keywords: Sewage; Nitrogen; Waste Disposal, Fluid; Carbon; Bioreactors; Ammonia; Soil Pollutants; Anaerobiosis